Health screening needs independent regular re-evaluation. (27th September 2021) - Ropers, Fabienne G; Barratt, Alexandra; Wilt, Timothy J; Nicholls, Stuart G; Taylor-Phillips, Sian; Kramer, Barnett S; Esserman, Laura J; Norris, Susan L; Gibson, Lorna M; Harris, Russell P; Carter, Stacy M; Jacklyn, Gemma; et al.
Abstract : Changing circumstances may alter the benefit and risk profile of screening programmes. Fabienne G Ropers and colleagues propose a framework for re-evaluation to ensure continued public benefit